RESPONS PETANI TERHADAP INOVASI BUDIDAYA DAN PEMANFAATAN SORGUM DI KECAMATAN SRANDAKAN KABUPATEN BANTUL - Alvitri Wijayanti; Subejo Subejo; Harsoyo Harsoyo (Agro Ekonomi, 2015)
This research was conducted in Poncosari Village, Srandakan Sub District, Bantul Regency. Poncosari Village is an area that farmers cultivate sorghum. This research aims to determine the innovation cultivation and utilization of sorghum, the response of farmers to the innovation and utilization of sorghum and use the products for varrous purposive, and the factors that influence the response of farmers on cultivation innovation and they use of sorghum product in Srandakan Sub District, Bantul Regency. The research results showed that the response rate of cultivate innovation of sorghum farmers and utilization was 57.99%. Where 90% of the farmers are still hesitant to application innovation and utilization of sorghum cultivation. The eason that sorghum is a newdeveloped technology in the surveyed area. Perception and motivation in a positively and significantly influence to the response off armerson cultivation innovation and utilization of sorghum cultivation. Factors that did not significantly influence to the response on farmers cultivating innovation and utilization of sorghum areage, education, land lize, sorghum farming experience, and intensity extension activity.